2015
DOI: 10.1155/2015/646171
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Role of L-Carnitine in Skeletal Muscle Oxidative Stress and Atrophy Conditions

Abstract: The targeting of nutraceutical treatment to skeletal muscle damage is an emerging area of research, driven by the need for new therapies for a range of muscle-associated diseases. L-Carnitine (CARN) is an essential nutrient and plays a key role in mitochondrial β-oxidation and in the ubiquitin-proteasome system regulation. As a dietary supplement to improve athletic performance, CARN has been studied for its potential to enhance β-oxidation. However, CARN effects on myogenesis, mitochondrial activity, and hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…In mice that are fed a high‐fructose diet which is known as an acquired model of insulin resistance, the presence of L‐carnitine reduced protein oxidation in the lens, and the decreased anti‐oxidative enzymes were recovered, thus preserving mitochondrial function 30. Moreover, the presence of L‐carnitine increases Akt phosphorylation and accelerates myotube formation in C2C12 cells31 and in the muscle of rats 32. These pleiotropic effects of L‐carnitine, including anti‐oxidative and anti‐inflammatory activities and maintaining Akt signaling, could play an important role in the protection of mitochondrial function in CKD conditions, especially in cases of higher IS accumulation, such as uremia.…”
Section: Discussionmentioning
confidence: 99%
“…In mice that are fed a high‐fructose diet which is known as an acquired model of insulin resistance, the presence of L‐carnitine reduced protein oxidation in the lens, and the decreased anti‐oxidative enzymes were recovered, thus preserving mitochondrial function 30. Moreover, the presence of L‐carnitine increases Akt phosphorylation and accelerates myotube formation in C2C12 cells31 and in the muscle of rats 32. These pleiotropic effects of L‐carnitine, including anti‐oxidative and anti‐inflammatory activities and maintaining Akt signaling, could play an important role in the protection of mitochondrial function in CKD conditions, especially in cases of higher IS accumulation, such as uremia.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that COM attachment activated Akt/GSK-3β and Snail signaling, PI3K/Akt pharmacological inhibitor could abolish these alters and inhibit dedifferentiation, indicating that Akt/GSK3β/Snail signaling plays an overarching role in COM-induced dedifferentiation. Relationships of L-carnitine and Akt/GSK3β have been reported to be contradictory in several pathogenesises [26][27][28], but whether L-carnitine is able to protect MDCK cells from COM-induced dedifferentiation through Akt/GSK3β/Snail signaling is uncertainty. In our study, L-carnitine attenuated the COM-induced activating of Akt/GSK3β/Snail signaling, considering Akt/GSK3β/Snail signaling as a contributor to the inhibitory effect of L-carnitine on cell dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…1a. These doses were chosen based on literature data [18,19]. We studied HepG2 growth capacity to evaluate the absence of cytotoxic effects.…”
Section: Cell Line Culture Conditionsmentioning
confidence: 99%
“…Our group has recently demonstrated that LC could regulate cellular anti-oxidative responses [18][19][20]26]. Since mitochondria are the primary intracellular regulator of ROS balance, LC effect on mitochondrial activity in HepG2 cells was studied.…”
Section: L-carnitine Effects On Mitochondrial Biogenesis and Anti-oximentioning
confidence: 99%
See 1 more Smart Citation